Avaliação morfológica do terço apical de canais radiculares retos e curvos após ampliação foraminal - Epaminondas, Maria Lúcia Vieira (2020)
Foraminal enlargement (FE) refers to the mechanical enlargement of the apical foramen during a root canal instrumentation step. It is a technique that deserves discussion because there is little scientific evidence on its clinical application. Therefore, the aim of the present study was to evaluate the morphological changes of the apical third of the root canal and formation of dentinal microcracks after FE in straight and curved root canals, through scanning electron microscopy (SEM) and micro-computed tomography (micro-CT) analyses. Sixty teeth were selected and divided in four experimental groups: GI-SEM (incisors / n = 15), GM-SEM (molars / n = 15), GI-MCT (incisors / n = 15) and GM-MCT (molars / n = 15). The incisors and mesio-buccal molars canals were instrumented in the apical foramen and 1mm beyond. In the SEM, the occurrence of foraminal deformation were verified and for MicroCT, it was observed the presence of microcracks in the root apical third. The Z statistical test was used to analyze if there was differences in the deformation ratio in the different groups after SEM analysis ( = 0.05). The number of microcracks identified in the pre and post-instrumentation images were calculated and presented as a percentage. The curvature of the canal did not influence the occurrence of foraminal deformation either for instrumentation in the foramen or for instrumentation beyond the foramen (p>0.05). It was also observed that the increase in working length did not influence the appearance of new deformations in GI-SEM and in GM-SEM (p>0.05). Qualitative microCT analysis showed the presence of dentinal defects in 0.8% (112) and 1.5% (208) of the cross-sections of incisors and molars, respectively, from a total of 13,987 slices. All dentinal defects identified in the analysis of any postoperative scans were already present in the corresponding preoperative images. Therefore, no new microcracks were observed after root canal preparation. Thus, it can be concluded that root canal curvature neither the level of WL influenced the occurrence of deformation in the apical foramen. There is a lack of causal relationship between foraminal enlargement at different levels and dentinal microcracks.